Factors Influencing Pneumonia Recurrence in Children Under Five Years at Lingsar and Sigerongan Health Center - Fathinah Salsabilla Hairy; Linda Silvana Sari; Titi Pambudi Karuniawaty (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
World Health Organization (WHO) labels pneumonia as “the leading killer of children worldwide” because for every five deaths of children under five, one is caused by pneumonia. According to WHO, pneumonia is the main cause of death in children less than five years old in developing countries. Based on Indonesia's health profile in 2020, pneumonia is the main problem causing death in children aged 29 days - 11 months with a prevalence of 14.5% or the equivalent of 3.55 per 100 children under five. Data from the West Nusa Tenggara health service in 2023 recorded 31,035 cases of pneumonia in children under five in NTB. The aim of this study was to determine the factors that influence the recurrence of pneumonia in toddlers in the Sigerongan and Lingsar Community Health Center Working Areas. This research is a observational analytical research with a Case Control design. The sampling technique uses Consecutive Sampling until the required sample is reached. The research was conducted in the work area of the Sigerongan and Lingsar Health Centers in West Lombok with a research sample of 84 respondents. The data obtained was analyzed using tests Chi-Square, Fisher’s exact, and Kolmogorov Smirnov. The results of the bivariate analysis using the testwho square, Fisher’s exact, And Kolmogorov Smirnov shows the completeness factor of immunization (p-value0.532), exclusive breastfeeding (p-value0.698), LBW (p-value0.395), nutritional status (p-value0.000), time to start MPASI (p-value 0.698), comorbidities (p-value 0.296), residential density (p-value0.549), smoking behavior (p-value 0.443), duration of smoking (p-value0.278), smoking area (p-value0.000), smoking dependence (p-value 0.000), parents education (p-value0.000), and home environment (p-value 0.616) does not affect pneumonia recurrence The results show that residential density factors influence the recurrence of pneumonia in children under five years.